A Clinical Investigation on ADHD-Traits in Childhood Celiac Disease. Issue 4 (February 2023) - Efe, Ayşegül; Tok, Ayşegül
Objective: There are no definitive results about either the presence of exact comorbidity between celiac disease (CD) and attention-deficit/hyperactivity disorders (ADHD) or etiology. We intend to screen ADHD-related cognitive and behavioral traits in children with biopsy-proven CD and investigate the possible association of these traits with certain vitamin levels, body-mass index, and gluten-free diet (GFD) compliance. Method: A total of 85 children with biopsy-proven CD (the ages of 8–18 years) were compared with age and sex-matched 72 healthy controls in terms of demographics, psychiatric symptoms, certain vitamin levels, and anthropometric measurements. Results: ADHD-like cognitive issues, such as inattention and learning difficulties, as well as psychosomatic symptoms and poor prosocial behavior, were all associated with GFD noncompliance in childhood CD. Conclusion: Untreated CD may predispose to ADHD-resembling symptoms. Physicians should be aware of the probability of ADHD misdiagnosing due to ADHD-resembling cognitive and behavioral traits in untreated CD.